Boosting ferroptosis and microtubule inhibition for antitumor therapy via a carrier-free supermolecule nanoreactor - Min Mu; Xiaoyan Liang; Na Zhao; Di Chuan; Bo Chen; Shasha Zhao; Guoqing Wang; Rangrang Fan; Bingwen Zou; Bo Han; Gang Guo (Elsevier, 2023)
Traditional microtubule inhibitors fail to significantly enhance the effect of colorectal cancer; hence, new and efficient strategies are necessary. In this study, a supramolecular nanoreactor (DOC@TA-Fe3+) based on tannic acid (TA), iron ion (Fe3+), and docetaxel (DOC) with microtubule inhibition, reactive oxygen species (ROS) generation, and glutathione peroxidase 4 (GPX4) inhibition, is prepared for ferroptosis/apoptosis treatment. After internalization by CT26 cells, the DOC@TA-Fe3+ nanoreactor escapes from the lysosomes to release payloads. The subsequent Fe3+/Fe2+ conversion mediated by TA reducibility can trigger the Fenton reaction to enhance the ROS concentration. Additionally, Fe3+ can consume glutathione to repress the activity of GPX4 to induce ferroptosis. Meanwhile, the released DOC controls microtubule dynamics to activate the apoptosis pathway. The superior in vivo antitumor efficacy of DOC@TA-Fe3+ nanoreactor in terms of tumor growth inhibition and improved survival is verified in CT26 tumor-bearing mouse model. Therefore, the nanoreactor can act as an effective apoptosis and ferroptosis inducer for application in colorectal cancer therapy.